2019
DOI: 10.3390/foods8100443
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pseudocereals Preferment Made with Aromatic Yeast Strains for Enhancing Wheat Bread Quality

Abstract: Usually, aromatic yeasts are designed to ferment wheat substrates for baking purposes but identification of new substrates for these strains and consequently new formulations for dough could lead to diversified bakery products with improved nutritional qualities and specific sensorial properties. The purpose of our study was to optimize the fermentation of quinoa and amaranth flours with non-conventional yeast strains in order to obtain a preferment with high potential in enhancing nutritional, textural and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Reviewing the existent literature regarding some of the most studied NFCBs, it is shown that they are usually based on barley, maize, millet, oats, rice, rye, sorghum, and wheat [27,28]. Cereals are known as important sources of dietary proteins [29], energy, carbohydrates, vitamins, minerals, and fibre (arabinoxylan and β-glucan), but, at the same time, they are deficient in some basic components (essential amino acids, e.g., lysine) [19,30]. Whole grains are known to have important bioactive compounds and high nutritional values and their regular consumption has a positive effect on health [31][32][33].…”
Section: An Overview Of Nfcbsmentioning
confidence: 99%
“…Reviewing the existent literature regarding some of the most studied NFCBs, it is shown that they are usually based on barley, maize, millet, oats, rice, rye, sorghum, and wheat [27,28]. Cereals are known as important sources of dietary proteins [29], energy, carbohydrates, vitamins, minerals, and fibre (arabinoxylan and β-glucan), but, at the same time, they are deficient in some basic components (essential amino acids, e.g., lysine) [19,30]. Whole grains are known to have important bioactive compounds and high nutritional values and their regular consumption has a positive effect on health [31][32][33].…”
Section: An Overview Of Nfcbsmentioning
confidence: 99%
“…Springiness measures the elasticity and is the height that the food recovers during the time that elapses between the end of the first compression and the start of the second compression. It is an important mechanical characteristic that has been associated with the elastic and fresh aerated product by [48] and together with resilience could be used to describe crumb elasticity [49]. Resilience is the ratio of recoverable energy as the first compression is relieved, a lower value indicating that the muffins need more time to return to the initial form and chewiness (product of hardness × cohesiveness × springiness.…”
Section: Texture Profile Analysismentioning
confidence: 99%
“…Several studies search for alternative ingredients (i.e., amaranth, aleurone, potato, quinoa, etc.) as a substitute, in bakery products to increase its nutritional quality [ 5 , 6 , 7 , 8 ]. Soybean ( Glycine max L.) is part of the Fabaceae family, with particularly high nutrient content like carbohydrates, lipids, proteins, minerals, fibers, vitamins, and has low saturated fat content [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%